2013
DOI: 10.1128/jvi.00159-13
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Element in Human Interleukin 6 Confers Escape from Degradation by the Gammaherpesvirus SOX Protein

Abstract: Several viruses express factors to silence host gene expression via widespread mRNA degradation. This phenotype is the result of the coordinated activity of the viral endonuclease SOX and the cellular RNA degradation enzyme Xrn1 during lytic Kaposi's sarcoma-associated herpesvirus (KSHV) infection. While most cellular transcripts are highly downregulated, a subset of host mRNA escapes turnover via unknown mechanisms. One of the most prominent escapees is the interleukin 6 (IL-6) mRNA, which accumulates robustl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 57 publications
5
76
0
Order By: Relevance
“…The IL-6 mRNA is directly refractory to SOX cleavage and thus remains robustly induced during host shutoff due to the presence of a specific 'SOX resistance element' (SRE) [26,29]. Even in the absence of infection, reporter mRNAs bearing the IL-6 SRE remain stable in SOX-expressing cells, an observation that has helped delineate features of this novel RNA element required for the protective phenotype [26,27].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The IL-6 mRNA is directly refractory to SOX cleavage and thus remains robustly induced during host shutoff due to the presence of a specific 'SOX resistance element' (SRE) [26,29]. Even in the absence of infection, reporter mRNAs bearing the IL-6 SRE remain stable in SOX-expressing cells, an observation that has helped delineate features of this novel RNA element required for the protective phenotype [26,27].…”
Section: Introductionmentioning
confidence: 96%
“…Studying these 'escapees' in aggregate is complicated, however, by the fact that multiple mechanisms can promote apparent escape. These include lack of a targeting motif, indirect transcriptional effects, and active evasion of cleavage [22,[24][25][26][27][28]. This latter phenotype, termed dominant escape, is particularly notable as it involves a specific RNA element whose presence in the 3' UTR of an mRNA protects against SOX cleavage, regardless of whether the RNA contains a targeting motif.…”
Section: Introductionmentioning
confidence: 99%
“…Glaunsinger and colleagues identified a host shutoff activity during KSHV lytic infection whereby a majority of transcripts of both host and viral origins are subject to turnover, resulting in their decreased steady-state levels. A minority of host transcripts have been shown to escape host shutoff (73,74), and at least one of these, the interleukin-6 (IL-6) transcript, does so in a manner involving its 3= UTR (75). It is currently unknown whether viral transcripts escape shutoff-mediated turnover, and it has been suggested that some viral transcripts need not escape turnover since they are transcribed at high levels during lytic infection (76).…”
Section: Figmentioning
confidence: 99%
“…A more immediate and timely response is translational upregulation or maintenance of the levels of existing mRNAs. Induction or maintenance of mRNA levels of some specific genes has been observed during host shutoff caused by a number of viral infections (18)(19)(20). For example, lytic replication of Kaposi's sarcoma-associated herpesvirus (KSHV) induces host shutoff because a virus-encoded SOX endonuclease degrades host mRNAs.…”
Section: ) (1)mentioning
confidence: 99%
“…For example, lytic replication of Kaposi's sarcoma-associated herpesvirus (KSHV) induces host shutoff because a virus-encoded SOX endonuclease degrades host mRNAs. The infection also induces transcription of interleukin-6 (IL-6), and IL-6 is resistant to SOX-induced RNA degradation (18,19). In the case of herpes simplex virus, a virally encoded endoribonuclease degrades most cellular mRNAs, but it spares a small number of cellular mRNAs (20).…”
Section: ) (1)mentioning
confidence: 99%